Prevzemi - instituti prevzemnega prava skozi prizmo pravne teorije in sodne prakse - Krneža, Lara (Podjetje in delo, 2022)
The authors examine the institute of takeover of a capital company, which they support with legislation and the relevant, yet different cases from Slovenian and EU case law. An important aspect that the authors are emphasising in the article is the protection of the interests of minority shareholders, their assets and corporate rights. To insure the latter, the Takeovers Act (ZPre-1) of 2006 and Directive 2004/25/EC of the European Parliament and of the Council on takeover bids are significant. The authors explain the institute of takeover through the concepts of target company, takeover bid and takeover threshold. Mainly, they focus on the takeover bid and, in its regard, they try to explain its impact on the acquirer and the possible influences on minority shareholders.
Keywords: Directive on Takeover Bids; Direktiva o ponudbah za prevzem; mandatory takeover bid; manjšinski delničarji; minority shareholders; offeror; prevzem; prevzemna ponudba; prevzemni prag; prevzemnik; takeover; takeover threshold; Zakon o prevzemih